Pendidikan Toleransi dan Praktik Beragama Masyarakat di Kampung Jawa Bali - Sumadi, Eko; Masrufah, Amirotul; Fitriyah, Roudlotun Nuril; Lami'ah, Sirojatul; Solahiya, Ananda Iffa; Muazizah, Siti (LP2M IAIN kUDUS, 2022)
The purpose of this study is to explain the forms of tolerance in Kampung Jawa as well as the driving and inhibiting factors of community tolerance by using a case study in Wanasari Hamlet. In this hamlet, the non-Muslim community and the people of Kampung Jawa live in harmony. The survey method used is a qualitative survey method, and data collection is done by qualitative descriptive and interviews with several informants in Kampung Jawa. The results obtained from this study are that the practice of religious tolerance in Kampung Jawa is going well, because the attitude of community tolerance is very high. The people of Wanasari Hamlet in carrying out religious activities can run smoothly and peacefully, besides that they are also invited in the form of mutual cooperation activities, festivals, village celebrations or traditional ceremonies between religious communities in Kampung Jawa. It can be used as a support to create a peaceful life, full of tolerance and harmony.